Development of Islamic Education Teachers' Professionalism in the Digital Era - Istighosah (International Journal of Islamic Pedagogical Research, 2025)
This study investigates the development of professional competence among Islamic Education (PAI) teachers at SMA Islam Al Fattah, driven by challenges such as limited time for professional development, unequal digital literacy, and insufficient long-term external support. Using a qualitative descriptive approach, data were collected through interviews, observations, and documentation to analyze how institutional support, teacher motivation, and the school’s religious culture contribute to professional growth. The findings show that the school implements three key strategies: continuous training and workshops, structured mentoring and academic supervision, and sustained self-development through religious activities and participation in professional communities. These efforts enhance teachers’ pedagogical, professional, social, and spiritual competencies. The study also identifies the impact of managerial support, availability of technological facilities, and collaborative work culture as significant factors in strengthening teacher professionalism. However, constraints such as heavy workloads, limited technological mastery, and inconsistent external professional programs still hinder optimal development. The implications of this research highlight the need for integrated and collaborative policies between schools, government agencies, and professional communities to ensure continuous teacher development. Strengthening digital literacy, expanding long-term mentoring programs, and providing adequate incentives are essential to producing PAI teachers who are competent, ethical, and adaptive to educational changes